Animated Video Media With Indonesian Folklore To Improve Reading Literacy In Grade Iii Elementary Schools - Anggraeni, Ni Kadek Julia Putri; Astawan, I Gede; Tristiantari, Ni Ketut Desia (International Journal of Language and Literature, 2024)
This research is motivated by the low interest and literacy skills of third-grade elementary school students. One of the causes is the limited interesting and contextual learning media. The purpose of this study was to analyze the effectiveness of animated video media containing Nusantara folklore in improving students' reading literacy. The development model used is the ADDIE model (analyze, design, development, implementation, evaluation). The subjects of the study were 43 third-grade students divided into control and experimental classes. The data collection methods and instruments used were questionnaires and essay-based literacy test questions. The data analysis techniques used in this development research were qualitative descriptive analysis methods and quantitative descriptive analysis. The results of the Independent Sample t-test assisted by IBM SPSS Statistics obtained Sig. (2-tailed) results of 0.000 and Sig. <0.05, then H0 is rejected and H1 is accepted. Animated video media containing Nusantara folklore is valid and practical to use and effective in improving students' reading literacy skills. The implications of this research show that the integration of local cultural values ​​through interactive visual media is able to create fun and meaningful learning for elementary school students.